Migration, Ethnicity, and the Educational Gradient in the Jakarta Mega-Urban Region: A Spatial Analysis. Issue 1 (2nd January 2016) - Jones, Gavin W.; Rangkuti, Hasnani; Utomo, Ariane; McDonald, Peter
Abstract : The Jakarta mega-urban region (MUR) is one of the largest such regions in the world. In this article, we revisit Castles's seminal 1967 article, based on the 1961 Population Census of Indonesia, on the educational and ethnic composition of Jakarta. Using data from the full-count 2010 Population Census, we examine spatial patterns in the educational gradients of the population across the Jakarta MUR and look to determine whether these patterns can be explained by internal migration and ethnic composition at the kecamatan (subdistrict) level. We find that population movement from the core to the outer areas has softened the historically extremely sharp gradation in educational attainment across the MUR. We show the dominance of the Sundanese and Bantenese ethnic groups in the rural hinterlands of the MUR, where the average educational attainment is relatively low, and note this question of rurality versus ethnicity when interpreting our results.